First report of liver abscesses due to Streptococcus intermedius of periodontal origin in Venezuela - Castillo Ayala, Daniel; De Andrade, Yuraima P.; Traviezo, Luis E. (Revista Gregoriana de Ciencias de la Salud, 2024)
Streptococcus intermedius belongs to the Streptococcus anginosus subgroup, being a beta-hemolytic, catalase-negative, non-motile and Gram-positive bacteria, which in comparison with the other members of this group (Streptococcus anginosus and Streptococcus constellatus) tends to greatly enhance infections. S. intermedius was associated with liver abscesses following dental, intestinal infections, intestinal or colorectal tumors. The present case treated a 44-year-old male patient who attended the referred hospital with fever, hepatomegaly, and abdominal pain for one month. An abdominal ultrasound and computed axial tomography of the abdomen were performed, revealing liver abscesses produced by S. intermedius (blood culture). The treatment of choice was a combination of drainage, surgery and antibiotic therapy.